ΔGABAA Receptors Are Necessary for Synaptic Plasticity in the Hippocampus: Implications for Memory Behavior. (November 2016) - Whissell, Paul D.; Avramescu, Sinziana; Wang, Dian-Shi; Orser, Beverley A.
Abstract : BACKGROUND: Extrasynaptic γ-aminobutyric acid type A (GABAA ) receptors that contain the δ subunit (δGABAA receptors) contribute to memory performance. Dysregulation of δGABAA receptor expression, which occurs in some neurological disorders, is associated with memory impairment. Mice lacking δGABAA receptors ( Gabrd −/− ) exhibit deficits in their ability to distinguish between similar memories, a process which is referred to as pattern separation. The CA3 and dentate gyrus subfields of the hippocampus regulate pattern separation, raising the possibility that synaptic plasticity is impaired in these regions in Gabrd −/− mice. Although long-term potentiation (LTP), the most widely studied form of synaptic plasticity, is normal in the dentate gyrus of Gabrd −/− mice, LTP in the CA3 subfield has not been studied. Here, we tested the hypothesis that LTP is reduced in the CA3 subfield of Gabrd −/− mice. METHODS: LTP of extracellular field postsynaptic potentials was studied in the mossy fiber (MF)-CA3 pathway using hippocampal slices from Gabrd −/− and wild-type (WT) mice. We also examined paired pulse responses and input–output relationships at MF-CA3 synapses. RESULTS: MF-CA3 LTP was reduced in Gabrd −/− mice, as evidenced by decreased potentiation of field postsynaptic potentials (WT: 178.3% ± 16.1% versus Gabrd −/− : 126.3% ± 6.9%; P = 0.0091). Thus, the deletion of δGABAA receptors is associated with impaired plasticity. Bicuculline (BIC), a GABAA receptor antagonist, reduced plasticity in WT but not in Gabrd −/− mice (WT + BIC: 123.9% ± 7.6% versus Gabrd −/− + BIC: 136.5% ± 7.0%). Paired pulse responses and input–output relationships did not differ between the genotypes (all P s > 0.05). CONCLUSIONS: Both genetic deletion and pharmacological blockade of δGABAA receptors impair MF-CA3 LTP, suggesting that δGABAA receptors are necessary for synaptic plasticity in the CA3 subfield. Drugs that enhance δGABAA receptor function may reverse deficits in synaptic plasticity in the CA3 subfield and improve pattern separation in neurological disorders. Abstract : Published ahead of print July 26, 2016.